Effect of Pruning and Micronutrient Sprays on Physico-chemical Properties of Ber - , Bhaskarjyoti Sarma; , U. Kotoky; , A. Saikia; , R. Sarma; , S. Saha; , M. Choudhury; , J. Moshahary (Archives of Current Research International, 2024)
An investigation was undertaken to study the effect of pruning height and micronutrients on the physicochemical properties of ber. The experiment was conducted in the farmer’s field at Manikpur area of Bongaigaon district, Assam (26026¢51² North latitude and 90046¢47² East longitude) for two consecutive years. Two types of Thailand ber were exposed to two different pruning heights and eight different micronutrient spray combinations. Results depicted that Roundish ovate reddish type variety performed better. The highest total sugar content (14.91%), TSS/acid ratio (44.07) and ash content (2.66%) were observed at a pruning height of 75 cm. Among micronutrients, borax at 0.5% and zinc sulphate (ZnSO4) at 0.5% in combination proved to be better in terms of total sugar (14.83%) and ash content (2.64%). So, the experiment proved that a pruning height of 75 cm from the ground level and spraying of borax 0.5% and zinc sulphate 0.5% in combination, were better compared to the other treatments.